Novel dual-layer hollow fiber membranes applied for forward osmosis process - Setiawan, Laurentia (2013)
A novel dual-layer forward osmosis (FO) hollow fiber membrane has been designed and successfully fabricated by using a triple orifice spinneret. The fiber consists of two layers made from polyamide-imide (PAI) polymer for the outer layer and polyethersulfone (PES) polymer for the porous inner layer. Specifically, after obtaining asymmetric microporous PAI/PES dual-layer hollow fibers via non-solvent induced phase inversion, polyethyleneimine (PEI) polyelectrolyte modification on the outer PAI layer was applied to produce a nanofiltration (NF)-like thin layer, while the PES porous inner layer remained intact as PES is inert to PEI. The membrane morphology, structure and surface property were carefully tailored by adjusting polymer dope composition and spinning conditions. These membranes were subsequently characterized by a series of standard protocols in terms of membrane structure, permeability and salt rejection, and were utilized in FO process.